(untitled) (International Journal of Engineering Management Science, 2019)
The increasing accumulation of iron ore mine tailings and the depletion of natural construction materials have necessitated the exploration of sustainable alternatives for civil engineering applications. This study presents an experimental investigation on the geotechnical and mechanical properties of iron ore mine tailings to evaluate their suitability for use in concrete and construction-related works. Iron ore mine tailings were characterized for their physical, chemical, and mineralogical properties and were used as partial replacements for natural fine aggregates in concrete at varying proportions. Geotechnical behavior was assessed through compaction and shear strength tests, while mechanical performance was evaluated using compressive, split tensile, and flexural strength tests. Durability characteristics were examined through water absorption and sorptivity measurements. The results indicate that concrete incorporating iron ore mine tailings at replacement levels up to 20% exhibits comparable or improved mechanical performance relative to conventional concrete, attributed to enhanced particle packing and matrix densification. Geotechnical test results further demonstrate favorable compaction characteristics and improved shear resistance, particularly when tailings are stabilized. However, higher replacement levels resulted in reduced workability and increased permeability. Overall, the findings confirm that iron ore mine tailings can be effectively utilized as a sustainable alternative material in concrete and geotechnical applications, contributing to waste reduction and resource conservation in the construction industry.